Advancing Diagnosis: The Role of Imaging Modalities in Accurate Assessment of Skull Base ENT Pathologies: Imaging Modalities in Skull Base Ear Nose and Throat Pathologies - Hussain, Ashfaq; Hussain, Junaid; Mushtaq, Allah Bux; Ashraf, Safia; Siddique, Tariq Zia; Afzal, Muhammad (Pakistan Journal of Health Sciences, 2024)
The skull base was a multifaceted anatomical region where important structures unite, including major blood vessels and cranial nerves. Precise diagnosis of Ear, Nose, and Throat disorders in this area was critical for effective treatment planning, but conventional diagnostic methods often lack the required detail. Objective: To determine the efficiency of Computed Tomography and Magnetic Resonance Imaging in correctly diagnosing skull base Ear, Nose, and Throat pathologies. Methods: A comparative study was carried out at Shahida Islam Medical Complex, Lodhran, from September 2023 to February 2024. A purposive sampling technique was used to select 100 patients who underwent Computed Tomography and Magnetic Resonance Imaging for suspected skull base Ear, Nose, and Throat pathologies. Imaging results were compared against final clinical diagnoses confirmed through biopsy. Diagnostic accuracy was measured using sensitivity, specificity, Positive Predictive Value, and Negative Predictive Value. Statistical analysis was performed using SPSS version 25.0. Results: Magnetic Resonance Imaging showed higher sensitivity (85.7%) and specificity (87.7%) compared to Computed Tomography (sensitivity 73.0%, specificity 82.0% respectively). Diagnostic accuracy of Magnetic Resonance Imaging for specific pathologies included meningioma (sensitivity 93.52%, specificity 87.32%), chordoma (sensitivity 79.92%, specificity 95.72%), and nasopharyngeal carcinoma (sensitivity 86.62%, specificity 83.12%). Conclusions: It was concluded that Magnetic Resonance Imaging demonstrated higher diagnostic accuracy compared to Computed Tomography in the diagnosis of Ear, Nose, and Throat pathologies of skull base due to having greater sensitivity and specificity. These findings indicate that Magnetic Resonance Imaging is a superior diagnostic tool for early detection of skull base disorders.